2019
DOI: 10.1080/13102818.2019.1691466
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of genetic diversity inTriticum urartuThumanjan ex Gandilyan accessions using start codon targeted polymorphism (SCoT) and CAAT-box derived polymorphism (CBDP) markers

Abstract: Gomarian (2019) Assessment of genetic diversity in Triticumurartu Thumanjan ex Gandilyan accessions using start codon targeted polymorphism (SCoT) and CAAT-box derived polymorphism (CBDP) markers,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 36 publications
4
3
0
Order By: Relevance
“…In the same context, the average PIC value for SCoT markers (0.71) was higher than ISSR (0.69), suggesting a good capacity of the SCoT system to present the polymorphic level in the investigated genotypes. Similar results were revealed by [ 51 ]. Furthermore, the higher number of alleles per locus and number of effective alleles, the more polymorphic was the population and reflected the size of the population variation.…”
Section: Discussionsupporting
confidence: 92%
“…In the same context, the average PIC value for SCoT markers (0.71) was higher than ISSR (0.69), suggesting a good capacity of the SCoT system to present the polymorphic level in the investigated genotypes. Similar results were revealed by [ 51 ]. Furthermore, the higher number of alleles per locus and number of effective alleles, the more polymorphic was the population and reflected the size of the population variation.…”
Section: Discussionsupporting
confidence: 92%
“…The authors indicated that Rp and MI could be the most important indices in determining marker efficiency, while the ISSR had a higher resolution than SCoT markers, as this was consistent with our findings. Also, the results of the present study confirmed the usefulness of these markers for identifying the genetic diversity of wheat and of its wild relative genotypes [41][42][43].…”
Section: Discussionsupporting
confidence: 82%
“…According to Etminan et al and Khodaee et al [25,62], Rp and MI were the most relevant indices for measuring marker efficiency, although the ISSR had a higher resolution than SCoT markers, contradicting our findings. Additionally, the current study's findings verified the utility of these markers for detecting wheat and its wild cousin genotypes' genetic diversity [63,64].…”
Section: Issr Resultssupporting
confidence: 72%